2023
DOI: 10.1021/acsomega.3c02232
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured CuO Thin-Film-Based Conductometric Sensors for Real-Time Tracking of Sweat Loss

Abstract: Enhanced sweat sensors lead to real-time, sustained, noninvasive tracking of sweat loss, ensure insight into individual health conditions at the molecular level, and have obtained prominent interest for their hopeful implementations in customized health tracking. Metal-oxide-based nanostructured electrochemical amperometric sensing materials are the best selection for continuous sweat monitoring devices owing to their high stability, high-sensing capacity, cost-effectiveness, miniaturization, and wide applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In connection with these features, the sensing ability of films can differentiate their properties. It has been reported that the morphological change strengthens the cohesion effect and plays a role in the change of the contact angle …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In connection with these features, the sensing ability of films can differentiate their properties. It has been reported that the morphological change strengthens the cohesion effect and plays a role in the change of the contact angle …”
Section: Resultsmentioning
confidence: 99%
“…We characterized the sweat loss tracking performance of the fabricated flexible devices by providing four different concentrations of artificial sweat samples that were dropped onto the devices. The sensing-response values are defined as eq S = I n o m I i I i where S is the sensing response value of the CuO thin film material to the artificial sweat solutions. I nom is the stable conductivity of the devices in the sweat solution implementation; I i is the steady conductivity of the device in air (without artificial sweat solution implementation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation